2022
DOI: 10.3389/fimmu.2022.1042406
|View full text |Cite
|
Sign up to set email alerts
|

Pre-existing humoral immunity to low pathogenic human coronaviruses exhibits limited cross-reactive antibodies response against SARS-CoV-2 in children

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection causes asymptomatic or mild symptoms, even rare hospitalization in children. A major concern is whether the pre-existing antibodies induced by low pathogenic human coronaviruses (LPH-CoVs) in children can cross-react with SARS-CoV-2. To address this unresolved question, we analyzed the pre-existing spike (S)-specific immunoglobin (Ig) G antibodies against LPH-CoVs and the cross-reactive antibodies against SARS-CoV-2 in 658 serum samples col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Studies also showed the presence of cross-reactive antibodies and T cells against SARS-CoV-2 by prior sCoVs infection ( 9 , 10 ), implying that the phenomenon of immune imprinting might also exist between the different coronaviruses. Indeed, some studies demonstrated that the different levels of pre-existing sCoVs-specific antibodies might be correlated with the susceptibility and disease severity of SARS-CoV-2 infections ( 11 , 12 ), and thus it is suggested that the prevalence of pre-existing sCoVs antibodies might be a potential factor to affect the discrepancy of COVID-19 pandemic and the effectiveness of COVID-19 vaccination among different regions ( 13 , 14 ). However, the existing literature is still limited regarding the pre-existing sCoVs-specific antibodies and their potential influence on SARS-CoV-2 infection and COVID-19 vaccination effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Studies also showed the presence of cross-reactive antibodies and T cells against SARS-CoV-2 by prior sCoVs infection ( 9 , 10 ), implying that the phenomenon of immune imprinting might also exist between the different coronaviruses. Indeed, some studies demonstrated that the different levels of pre-existing sCoVs-specific antibodies might be correlated with the susceptibility and disease severity of SARS-CoV-2 infections ( 11 , 12 ), and thus it is suggested that the prevalence of pre-existing sCoVs antibodies might be a potential factor to affect the discrepancy of COVID-19 pandemic and the effectiveness of COVID-19 vaccination among different regions ( 13 , 14 ). However, the existing literature is still limited regarding the pre-existing sCoVs-specific antibodies and their potential influence on SARS-CoV-2 infection and COVID-19 vaccination effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…10 NP IgM antibodies may be present in subjects who have had a recent SARS CoV-2 infection, although they also indicate infections caused by other low-pathogenicity coronaviruses (HCoV-229E, HCoV-NL63, HCoV-HKU1, HCoV-OC43) due to antigen cross-reaction. 11 In this study, 36 subjects (23.6%) were found to be positive for NP IgM antibodies and 16 (10.5%) to be positive for anti-RBD IgG plus NP IgM in the pre-vaccination sample, which suggests that the latter group had SARS-CoV-2 acute infection, without any apparent risk of exposure being detected. It is probable that workers who tested positive for NP IgM and negative for anti-RBD IgG were infected by other circulating coronaviruses during the seasonal period in which blood samples were collected (winter).…”
Section: Discussionmentioning
confidence: 49%
“…1A &B, the healthy controls already presented a considerable level of antibodies binding to the SARS-CoV-2 proteins and neutralizing pseudovirus particles. The pre-existing antibody response to the SARS-CoV-2 virus in pre-pandemic samples has also been described elsewhere [ [72] , [73] , [74] , [75] , [76] ], which is suspected to be the cross-reactive response from prior endemic corona virus infections. The high baseline titer might have reduced the power to detect increases of antibody responses to the infection.…”
Section: Discussionmentioning
confidence: 92%